Caracterização estrutural e propriedades mecânicas de pastas de cimento fabricadas por freeze-casting com diferentes tipos de adições - Priscila Alves da Silva Machado (2021)
Porous materials are characterized for being light, thermal and sound insulating and are widely used in the civil construction sector in coatings, sealing blocks and permeable paving. Freeze-casting is a method widely used in the production of porous ceramics and consists of freezing a suspension, organizing the solid particles, followed by the sublimation solvent under reduced pressure and, subsequently, in the sintering of the porous material. Aiming the study and development of cementitious materials with ordered porosity, samples of Portland cement pastes were produced, containing different mineral additions (silica fume, carbon nanotubes and iron ore residue), hardened using the conventional method and the freeze-casting method. The samples were characterized, and compared to each other, through mechanical strength tests and porosity measurements. According to the results, it was possible to conclude the technical feasibility of producing Portland cement structures, containing certain mineral additions using the freeze-casting process controlling the pore structure. The pastes produced by the freeze-casting process presented compressive strength properties superior to the values obtained in the pastes hardened by the conventional method, and the pastes with the highest amount of solid particles and containing the addition of silica fume showed the best results against the mechanical efforts. When using the freeze-casting process successfully, it has also been shown that mineral additions seem to be better integrated into the structure of the cement pastes.